Disciplinarização e cientificidade: a economia política e a nascente sociologia durante o estabelecimento das ciências humanas e sociais na Alemanha (1875-1920) - Ian Coelho de Souza Almeida (2020)
This dissertation analyzes the relationship between sociology and political economy in late-19th and early-20th century Germany. At this moment, sociology was still an infant and highly criticized discipline, while political political economy was already relevant politically and academically. At the same time, both disciplines were embedded in a discussion regarding the autonomy and scientificity of the social and human sciences. In this context, our intention is to connect two great debates. On one hand, we have the Methodenstreit between Schmoller, then leader of the dominant German Historical School of Economics, and Menger. In sum, Schmoller defends the historical method against Menger’s criticism. On the other hand, the debate to which Wilhelm Dilthey largely contributed: the emancipation and scientific recognition of the social and human sciences, which he names Geisteswissenschaften. Dilthey argues that this field has a specific object of study and method, the historical method. Herewith, we show how we can better understand the controversies within political economy when we are aware of the circumstances affecting the social sciences field in general. Thereafter, we present the work of Heinrich Dietzel, who seeks a conciliatory solution for the Methodenstreit while advancing his view of the proper manner to do economic theory, following the Ricardian perspective. Another author that pursues a solution for this methodological debate is Max Weber, a key figure in our discussion. We first address Weber’s work from his proximity to Heinrich Rickert. Rickert, one of the most notorious neo-Kantians authors, dedicates part of his endeavor to defend his version of the independent field of human and social sciences, the Kulturwissenschaften. His is critical of Dilthey’s epistemological differentiation and establishes the difference between natural and cultural sciences in methodological terms. Here our focus is to present how Weber’s criticism to Schmoller is related to Rickert’s criticism of Dilthey. Furthermore, Weber’s significance rests on his image as the father of sociology. The author, who for a long period worked as a political economist, had a major role in the development of sociology. We explore how Weber’s conception of sociology and political economy changed over time and how these disciplines were related to the construction of knowledge in the social sciences in general. Other authors, such as Georg Simmel and Werner Sombart, were as much or even more important than Weber in the process of institutionalization of sociology. We will discuss them in the context of disputes inside the German Society for Sociology (DGS), created in 1909, specially the so-called Werturteilsstreit. This debate is directly connected to the Methodenstreit and implies overcoming the mistakes perpetrated majorly, but not exclusively, by the German Historical School. This was a discussion about value neutrality in science, which became a touchstone in the social sciences at the time. Moreover, value neutrality is crucial for understanding how scientific specialization depended on overcoming Schmoller’s perspective, and also how it was essential for correcting the mistakes associated with the historical method. In this sense, Weberian sociology allowed for a solution to the Methodenstreit by concentrating in economic sociology those aspects of social reality that Schmoller would see as part of economic theory, while Menger would dismiss as outside the field of political economy. Lastly, we analyze the different sociological perspectives that co-existed in the DGS to show that, even though there was significant methodological pluralism, positions that went against scientific specialization were marginalized.